(untitled) (Mustansiria Dental Journal, 2004)
The possibility of employing the frontal sinus ni orthodontic diagnosis and treatment planning has been verified. The frontal sinus width, maxillary, and mandibular base lengths have been determined cephalometrically from a sample of 73 Iraqi orthodontic patients aged 1 - 51 years, ranked into skeletal classes ,I I and I. The results showed increased frontal sinus width in class I and IlI subjects, ni addition to a significant correlation between frontal sinus enlargement and the increased jaw bone length. It has been concluded that the frontal sinus, as seen on lateral cephalogram, can be utilized clinically as an aid ni orthodontic diagnosis and treatment planning